Challenging lymphoid malignancy of primary central nervous system lymphoma: A case report - Kasinathan, Ganesh (Ann Med Surg (Lond), 2020)
INTRODUCTION: Primary central nervous lymphoma is an aggressive disease without evidence of systemic spread with an annual incidence of 7 cases per 1,000,000 people in the United States. CASE PRESENTATION: A 68-year-old gentleman of Malay ethnicity presented with left sided weakness associated with reduced sensation for one month. The patient was healthy and denied any constitutional symptoms, joint pains, rash or seizures. There was no recent trauma. Physical examination revealed left upper and lower limb motor grade power of 3/5 with upper motor neurone weakness of the left facial nerve. He had brisk reflexes and an upgoing extensor plantar response. Brain imaging (Magnetic Resonance Imaging) showed two lesions: one occupying the right head of the caudate nucleus and the other seen at the right side of the body of the corpus callosum. Histomorphology and immunohistochemistry confirmed Diffuse Large B-Cell Lymphoma (DLBCL) of non-germinal center type. He was treated with De Angelis protocol which involves chemoradiotherapy consisting of high dose methotrexate and whole brain radiotherapy (WBRT), followed by high dose cytarabine. Brain imaging post chemoradiation showed complete remission. CONCLUSION: Prompt detection with appropriate therapeutic protocol could significantly minimise the permanent neurological deficits in patients with this rare and challenging lymphoid malignancy.